EVALUASI KEBUTUHAN, PENYEDIAAN DAN PEMBINAAN GURU PENDIDIKAN AGAMA ISLAM DI SEKOLAH: EVALUATION OF ISLAMIC TEACHER’S REQUIREMENTS, PROVISIONS AND DEVELOPMENT IN SCHOOL - Lisa' Diyah Ma'rifataini (Balai Penelitian dan Pengembangan Agama Jakarta, 2018)
A complaint on the lack of Islamic teachers at school is always heard in every opportunity. In terms of quantity, a requirement of Islamic teacher which has been spread out all over the media is based only by ratio, which hasn’t been done as it should. This research is to counting the requirement of Islamic teachers in 10 provinces based on PP 74 year 2008 about the requirement of teachers, knowing the provision of Islamic teachers and knowing about the pattern of the development of Islamic teachers and also knowing a few of policy options which has been done by the institute. The approaching of this research is using mix method, which the qualitative data that supported by many quantitative data. The result of this research showing; 1) In 10 provinces sample, there is a lack of Islamic teachers in every level of school (elementary school, junior high school, high school, and vocational high school) as much as 17.396 teachers). 2) In reality, the appointment of Islamic teacher’s position these days is done by Indonesian Ministry of Religious Affairs, the allowance of teacher’s profession in done by Indonesian Ministry of Religious Affairs, the educational of teacher’s profession by regional government still have a few disadvantages. 3) Promotional moratorium of teachers must be immediately revoked, remembering the urgent condition of the Islamic teachers. 4) The matter of the development and capacity improvement and also professionalism of Islamic teachers should be done by the strength of KKG and MGMP Islamic studies becomes the centre teacher’s resources. 5) This research is also having 4 policies option that can be taken by chairman of Indonesian Ministry of Religious Affairs with all of its advantages and disadvantages.